KONSEP RUMAH SAKIT SYARIAH DALAM TRANSFORMASI EKONOMI SYARIAH - Haqiqotus Sa'adah (LPPM Sekolah Tinggi Agama Islam Al-Utsmani Bondowoso, 2022)
This study aims to examine the concept of a sharia hospital in the transformation of the sharia economy, Indonesia is currently a developing country and is faced with the issue of improving health quality. According to the 2019 Global Health Security Index, Indonesia is ranked 30th out of 195 countries. This shows that the level of health in Indonesia is already good. Sharia health services primarily aim to provide great benefits to the people. Likewise with Shariah health services that are inclusive for everyone. In this study using qualitative research methods, the data sources used were MUKISI guidebooks and articles in journals related to the theme. The data collection technique was carried out by means of a literature review. The results in this study are that there are values ​​in sharia hospitals that refer to Islamic economic values, namely Islamic economics has the basic nature of Rabbani and Human economics, it is said to be Rabbani economics because Islamic economics is conditional with divine goals and values. While Islamic economics is said to be human economics because Islamic economics is implemented and intended for human benefit (Hulwati, 2009). This can be realized with the basic values ​​or principles of Islamic economics, namely the values ​​developed by Yusuf Qardhawi include uluhiyyah, insaniyyah, akhlaqiyyah, and washatiyyah, while Syed Nawab Haider Naqvi adds Islamic economic values, namely ikhtiyah, and masuliyyah (Djakfar, 2019).